2020
DOI: 10.1007/jhep01(2020)195
|View full text |Cite
|
Sign up to set email alerts
|

Superpotential of three dimensional $$ \mathcal{N} $$ = 1 heterotic supergravity

Abstract: We dimensionally reduce the ten dimensional heterotic supergravity action on spacetimes of the form M (2,1) × Y , where M (2,1) is three dimensional maximally symmetric Anti de Sitter or Minkowski space, and Y is a compact seven dimensional manifold with G 2 structure. In doing so, we derive the real superpotential functional of the corresponding three dimensional N = 1 theory. We confirm that extrema of this functional correspond to supersymmetric heterotic compactifications on manifolds of G 2 structure in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
(129 reference statements)
0
12
0
Order By: Relevance
“…We hope to return to this fascinating topic in the near future. Some interesting results on 3d, N = 1 theories coming from heterotic strings on G 2 manifolds were also discussed in [110][111][112].…”
Section: Jhep01(2021)158mentioning
confidence: 99%
“…We hope to return to this fascinating topic in the near future. Some interesting results on 3d, N = 1 theories coming from heterotic strings on G 2 manifolds were also discussed in [110][111][112].…”
Section: Jhep01(2021)158mentioning
confidence: 99%
“…Because of the O-plane truncations, the preservation of supersymmetry on our background boils down to the supersymmetry Killing equations that arise from Type I string theory with F Y M = 0, which can in turn be related to Heterotic string theory via S-duality. Earlier work on Heterotic string flux compactifications [23], has shown that backgrounds with…”
Section: Supersymmetry Cross-checkmentioning
confidence: 99%
“…In other words H (HET) 3 ≡ T ( ) is identified with the full antisymmetric G2 torsion (2.7). In [23] the W 7 is also present and relates to the dilaton via dφ (HET) = 2W 7 , however, the specific orbifolding we use for our twisted torus projects it out, such that we are strictly working with a co-calibrated G2. In addition an external component of the H (HET) 3 flux is also allowed to be switched on, and is also related to the G2 torsion.…”
Section: Supersymmetry Cross-checkmentioning
confidence: 99%
See 2 more Smart Citations